2020
DOI: 10.1007/s10388-020-00721-0
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary team management for prevention of pneumonia and long-term weight loss after esophagectomy: a single-center retrospective study

Abstract: Background In April 2017, we launched the multidisciplinary Hamamatsu Perioperative Care Team (HOPE) for all surgical patients. We developed a reinforced intervention strategy, particularly for esophagectomy. We herein report the outcomes of the HOPE at 2 years after commencement. Methods A total 125 patients underwent esophagectomy and gastric conduit reconstruction for esophageal or esophagogastric junction cancer between January 2014 and December 2018 at the Department of Surgery in Hamamatsu University Sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Postoperative complications have been reported to worsen long‐term prognosis after surgery, 44 and their incidence has been reportedly reduced by the intervention of the multidisciplinary perioperative management team. 45 Thus, it is important to pay attention to perioperative care for patients with an elevated GPS for the reduction of postoperative complications and improvement of long‐term prognosis. Some research has reported that exercise and/or nutrition prehabilitation is associated with positive effects for weight maintenance and surgical complications.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative complications have been reported to worsen long‐term prognosis after surgery, 44 and their incidence has been reportedly reduced by the intervention of the multidisciplinary perioperative management team. 45 Thus, it is important to pay attention to perioperative care for patients with an elevated GPS for the reduction of postoperative complications and improvement of long‐term prognosis. Some research has reported that exercise and/or nutrition prehabilitation is associated with positive effects for weight maintenance and surgical complications.…”
Section: Discussionmentioning
confidence: 99%
“…In April 2017, we launched the multidisciplinary Hamamatsu Perioperative Care Team (HOPE) for all surgical patients [ 29 ]. Additionally, we developed a reinforced intervention strategy, particularly for esophagectomy.…”
Section: Multidisciplinary Team Management For Prevention Of Postoperative Complications After Esophagectomymentioning
confidence: 99%
“…The patients were categorized into the pre-HOPE group, including 62 patients who underwent esophagectomy before the formation of HOPE, and the HOPE group, including 63 patients who underwent esophagectomy after introducing HOPE. The incidence rates of postoperative pneumonia after esophagectomy (Clavien–Dindo classification grade 2 or higher) were significantly lower in the HOPE group (14%, 9/63) than in the pre-HOPE (29%, 18/62) group ( p = 0.037) [ 29 ]. The introduction of the multidisciplinary HOPE was associated with a significant reduction in postoperative pneumonia incidence, leading to improved long-term survival after esophagectomy [ 29 ].…”
Section: Multidisciplinary Team Management For Prevention Of Postoperative Complications After Esophagectomymentioning
confidence: 99%
See 2 more Smart Citations